Character Values in Pencak Silat Sports in the Context of Positive Youth Development - Risyanto, Aris; Subarjah, Herman; Ma'mun, Amung; Nuryadi, Nuryadi; Yulianto, Ari Gana; Prabowo, Indra (Universitas Majalengka, 2024)
Education has not achieved its maximum goals, especially noble morals and character. As a form of sport, Pencak Silat is believed to have several virtues that can change a student's character to be more positive. This research explores the character values ​​contained in the sport of Pencak Silat. Data collection methods and research instruments involve observation sheets and unstructured interviews. The research population included all pencak silat student-athletes at SMAN 1 Cibatu Purwakarta. The sampling technique uses a quota sampling technique. Data analysis techniques include data reduction, data presentation, and conclusion. The results of the research show that the character values ​​that exist in pencak silat sports include religion, honesty, tolerance, discipline, hard work, creativity, independence, democratic, curiosity, national spirit, love of the country, respect for achievement, friendly/communicative, loves peace, likes reading, cares about the environment, social care and responsibility.